PoSHAN Panel 2 Final Report. - Feed the Future Innovation Lab for Nutrition. (Tufts University. Tisch Library., 2016)
The goal of PoSHAN Community Studies is to understand the factors that link agriculture to nutrition. This involves researching the determinants of household food security, dietary intake, and nutritional status of children under 5 years of age and their mothers in relation to changes in agriculture and exposure to agricultural and microeconomic extension, as well as nutrition and health programs in Nepal. This descriptive report summarizes the main findings of the second panel survey conducted between May - July 2014.; Keywords: PoSHAN, Panel 2, Nepal, Agriculture, Nutrition, mother and child nutrition, maternal health, economics, health programs, food security, dietary diversity.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy